Perfil das demandas judiciais por medicamentos no Estado de São Paulo e Município de Botucatu - Costa, Guiomar Rufino da (2023)
Abstract Introduction: The Unified Health System (SUS), one of the largest public healthcare systems in the world, provides medications through Pharmaceutical Assistance. However, it faces challenges that lead to the pursuit of remedies through legal actions. This strains the healthcare system and results in additional expenditures. To improve this relationship, the Technical Support Center of the Judiciary (NatJus) was established, offering evidence-based guidance on recommended treatments in judicial decisions. Evaluating the demand for medication in legal actions and the impact of NatJus can lead to more effective solutions. Objectives: To assess the profile of judicial demands for medications in the State of São Paulo and Botucatu-SP, and the impact of NatJus implementation; to create an informative ebook about medication access in SUS. Methodology: The study examines legal proceedings for medication requests in São Paulo and Botucatu-SP. Data were collected from public sources under the Access to Information Law. The proceedings were evaluated in their entirety and grouped by health region in São Paulo. The financial impact was measured by the total amount awarded. The T-test compared the values of cases in the periods 2015-2016 (pre-NatJus) and 2019-2020 (post-NatJus). The evaluation of requested medications in successful cases was conducted through a sample calculation. Results: A total of 113,178 cases were observed in the state and 510 in the municipality of Botucatu, representing costs in the billions for the state and millions for Botucatu. The majority of claimants were in economically vulnerable situations. The assessment of NatJus implementation impact was hindered by the pandemic period. Cases with higher costs requested medications for Hepatitis C and Antineoplastics. In Botucatu, many legal actions sought medications from the basic pharmaceutical assistance. Conclusion: There was a high demand for legal proceedings in São Paulo and Botucatu, resulting in substantial expenses. Regional disparities in legal demands were identified in the state. In São Paulo, more expensive cases sought medications not available through SUS, whereas in Botucatu, many of the requested medications were already part of the basic program. This underscores the complexity of medication judicialization with regional variations. Collaborative dialogue between health and judiciary is important, as is informing the public about medication access through SUS. An informative ebook can raise awareness among users aboutthis issue.